2005
DOI: 10.1091/mbc.e04-09-0799
|View full text |Cite
|
Sign up to set email alerts
|

The Type Iα Inositol Polyphosphate 4-Phosphatase Generates and Terminates Phosphoinositide 3-Kinase Signals on Endosomes and the Plasma Membrane

Abstract: Endosomal trafficking is regulated by the recruitment of effector proteins to phosphatidylinositol 3-phosphate [PtdIns(3)P] on early endosomes. At the plasma membrane, phosphatidylinositol-(3,4)-bisphosphate [PtdIns(3,4)P2] binds the pleckstrin homology (PH) domain-containing proteins Akt and TAPP1. Type Iα inositol polyphosphate 4-phosphatase (4-phosphatase) dephosphorylates PtdIns(3,4)P2, forming PtdIns(3)P, but its subcellular localization is unknown. We report here in quiescent cells, the 4-phosphatase col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
91
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 51 publications
4
91
0
Order By: Relevance
“…INPP4A activity was measured based on indirect estimation of PtdIns(3)P; briefly, lung cytosols were prepared using mitochondria isolation kit (MITO-ISO1, Sigma Chemical Co.) and were incubated (37 °C for 1 h) with 2 µM PtdIns(3,4)P2 (substrate of INPP4A) in reaction buffer 48 and reaction products were further incubated with PtdIns(3)P detector protein, followed by transferring final products to PtdIns(3)P-coated microplate for competitive enzyme-linked immunosorbent assay (ELISA), and the final INPP4A activity was expressed as PtdIns(3)P in picomoles produced from PtdIns(3,4)P2. Calpain activity was performed using a calpain activity assay kit (BIOvision, Inc., Mountain View, CA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…INPP4A activity was measured based on indirect estimation of PtdIns(3)P; briefly, lung cytosols were prepared using mitochondria isolation kit (MITO-ISO1, Sigma Chemical Co.) and were incubated (37 °C for 1 h) with 2 µM PtdIns(3,4)P2 (substrate of INPP4A) in reaction buffer 48 and reaction products were further incubated with PtdIns(3)P detector protein, followed by transferring final products to PtdIns(3)P-coated microplate for competitive enzyme-linked immunosorbent assay (ELISA), and the final INPP4A activity was expressed as PtdIns(3)P in picomoles produced from PtdIns(3,4)P2. Calpain activity was performed using a calpain activity assay kit (BIOvision, Inc., Mountain View, CA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K activity generates phosphoinositides, which control cell survival, proliferation, migration and cellular trafficking (Cantley, 2002;Czech, 2003). Inositol polyphosphate-4-phosphatase is a regulator of PI3K, and it has been implicated in PI3K signaling at distinct subcellular junctions (Ivetac et al, 2005). Constitutive upregulation of cell-survival signaling mediated by PI3K/Akt has already been implicated in oncogenic transformation and tumor development, as it prevents apoptotic cell death during uncontrolled proliferation (Chang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PtdIns(3,4,5)P 3 accumulation after cell stimulation is immediate and transient, whereas PtdIns(3,4)P 2 accumulation is slightly delayed and significantly more sustained in platelets (6,7). Also, unlike PtdIns(3,4,5)P 3 that is primarily present in the plasma membrane, PtdIns(3,4)P 2 may be localized at endosomes, intralumi-nal vesicles, endoplasmic reticulum, as well as the plasma membrane (8).…”
mentioning
confidence: 94%